The 21 August 2017 Ischia (Italy) Earthquake Source Model Inferred From Seismological, GPS, and DInSAR Measurements. Issue 5 (2nd March 2018) - De Novellis, V.; Carlino, S.; Castaldo, R.; Tramelli, A.; De Luca, C.; Pino, N. A.; Pepe, S.; Convertito, V.; Zinno, I.; De Martino, P.; Bonano, M.; Giudicepietro, F.; et al.
Abstract: The causative source of the first damaging earthquake instrumentally recorded in the Island of Ischia, occurred on 21 August 2017, has been studied through a multiparametric geophysical approach. In order to investigate the source geometry and kinematics we exploit seismological, Global Positioning System, and Sentinel‐1 and COSMO‐SkyMed differential interferometric synthetic aperture radar coseismic measurements. Our results indicate that the retrieved solutions from the geodetic data modeling and the seismological data are plausible; in particular, the best fit solution consists of an E‐W striking, south dipping normal fault, with its center located at a depth of 800 m. Moreover, the retrieved causative fault is consistent with the rheological stratification of the crust in this zone. This study allows us to improve the knowledge of the volcano‐tectonic processes occurring on the Island, which is crucial for a better assessment of the seismic risk in the area. Key Points: Investigation of the ground deformation and source geometry of the 2017 Ischia Island earthquake (Italy) is discussed The available seismological, GPS, and DInSAR data permit to investigate the causative fault and define its geometry and kinematics The results suggest that the rheology properties of the crust beneath the Ischia Island have an influence on the volcano‐tectonic processes